Electronic Commerce in Singapore. - Lim, Shu Chen. (2008)
The objective of this project is to gain an overview and understanding of electronic commerce in Singapore. The Internet is poised to become an important business channel in the 21 st century. Internet electronic commerce is predicted to have exponential growth in the future and will have a significant impact on the way business is conducted. An understanding of the developments and uses of electronic commerce is essential for all business professionals.